PENGARUH PENAMBAHAN TEMPE TERHADAP DAYA TERIMA DAN KADAR AIR NUGGET JAMUR TIRAM - Cucuk Suprihartini; Frenky Arif Budiman; Yuli Umiarsih (STIKES dan AKZI Karya Husada Kediri, 2022)
Oyster mushroom nuggets with tempeh were processed food products that were processed from the basic ingredients of chicken, oyster mushrooms, tempeh, shallots, garlic, onion, wheat flour, and bread flour, tapioca flour, and eggs. Oyster mushroom nuggets are processed products using the addition of 0%, 10%, and 15% tempeh. This type of research uses experimental research. This study aims to determine the effect of adding tempeh on the acceptance and water content of oyster mushroom nuggets. This study uses a hedonic scale test for acceptance or organoleptic tests and a thermogravimetric test for water content. Organoleptic test using Friedman Test analysis with sig = 0. 05 and water content test using One Way Anova test with sig = 0. 01. If H0 was rejected, the Duncan test was continued. The results showed the effect of adding tempeh on color (sig 0. 00), aroma (sig 0. 00), taste (sig 0. 00), and there was no effect on texture (sig 0. 186) and water content (sig 0. 461). The percentage of panelists' acceptance of the most preferred color parameter was P0 with an acceptable value of 87%, the most preferred aroma was P0 of 88%, the most preferred texture was P0 of 89% and the most preferred taste was P1 of 89%. While the highest water content was found in P2 with a value of 37. 25%. It was suggested that further research needs to be carried out to test the shelf life and product innovation with natural ingredients in the nuggets.